TARGETED SURVEY AND REDISCOVERY EFFORT OF Papilio lampsacus, JAVAN ENDEMIC AND ENDANGERED BUTTERFLY SPECIES - Djunijanti Peggie; Imti Yazil Wafa; Nabila Rahma; Lutfi Irwansyah; Fariq Izzudien Ash Shidiq; Yohanes Agus Soenarko; Teguh Teguh; Abdul Mutholib Shahroni (BRIN Publishing (Penerbit BRIN), 2025)
Based on historical records and current data, this study examined the presence of Papilio lampsacus, a rare butterfly species in Java. From January to May 2024, four surveys were conducted at multiple sites in the Greater Bandung region of West Java. The natural forest edges and nearby agricultural landscape, where possible host and nectar plants are present, may indicate the possibility of finding the species. Despite repeated surveys under various weather conditions, no photographic evidence of P. lampsacus was obtained. However, brief visual encounters were recorded that were consistent with the species' appearance and flight patterns. Habitat assessments indicate the adverse effects of ongoing forest degradation and intensive pesticide use in agricultural areas adjacent to natural forests on butterflies. This study does not provide conclusive evidence confirming the existence of P. lampsacus. This highlights the importance of targeted long-term surveys, combined with well-managed habitats. These findings may serve as a basis to improve future monitoring approaches and conservation efforts for P. lampsacus and other rare butterflies.